PENINGKATAN MOTIVASI BELAJAR FISIKA SISWA DENGAN PENERAPAN STRATEGI PEMBELAJARAN TUTOR SEBAYA - Yennita '; Shinta Paramitha; Muhammad Sahal (Jurnal Pendidikan, 2013)
The main issue of this study was the view most of the students and communities that physics was a difficult subject and filled with so many formulas that cause students to be less motivated to learn physics, especially in senior high school. To increase student motivation, it was necessary to use innovative strategies in teaching physics. Has done a study of 65 students of class X SMA 8 Pekanbaru. The students were divided into two groups to determine the increase in motivation to learn physics with the implementation of peer tutoring strategies. ARCS motivation questionnaire used as research data collection instruments and the data was analyzed descriptively by calculating the gain motivation to learn phyiscs in the experimental group and the control group. The results of descriptive analysis showed that there was an increase in students' motivation of experiment group with motivation gain obtained amounting to 0.418 with a middle category. In the control group, as well as an increase in students' motivation to gain motivation of 0.244 with a low category. These results indicate that the use of peer tutors learning strategies in physics learning tend to increase the students' motivation. Keywords: physics teaching, learning motivation, peer tutoring